Forest Conversion in Upstream Oil and Gas Industry Area - Meyzi Heriyanto; Bayu Andrianto Wirawan; Darwis, AN (Publisher Cv. Inara, 2020)
Forest conversion is the root of the problem that can hamper investment, state revenue, and potentially cause state losses. The purpose of this study was to analyze forest conversion in the upstream oil and gas industry area and the factors that influence forest conversion in the upstream oil and gas industry area based on spatial analysis. This study used systematic sampling with the point grid method measuring 1 kilometers * 1 kilometers. Rokan Block had 5,125 sampling points. This study used raster-based GIS analysis and logistic regression with the Wald Test. The results of the study showed that the Rokan Block Area experienced a fairly severe forest conversion in 2000-2014 influenced by the total population and The 1986 TGHK. The novelty of this study is that the active role of communities around the forests that still upholds the concern for the forest must be preserved, because they will be the front guard in securing forest encroachment, and upstream oil and gas industry are not the main economic activities that cause forest conversion